Exploring Fibonacci Algebraic Equations and Their Application - Kumar, Nand Kishor; Prasad, Kripa Sindhu (Cognition, 2025)
This article explores the sequence’s generating functions, algebraic equations regulating it, and relationships to abstract algebra. Fibonacci algebra shows how patterns, numbers, and equations interact, from quadratic equations and generating functions to matrix algebra and beyond. Its simplicity and the surprising breadth of its linkages to other areas of mathematics are what give it its ongoing appeal. The study of Fibonacci algebraic equations is not just an exploration of an ancient sequence but a gateway to profound mathematical structures and applications. Whether through its connections to the golden ratio, matrix algebra, or advanced number theory, Fibonacci algebra continues to inspire and challenge mathematicians, offering a timeless bridge between elementary and advanced mathematics.